2003
DOI: 10.1056/nejmoa025313
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Heparin versus a Coumarin for the Prevention of Recurrent Venous Thromboembolism in Patients with Cancer

Abstract: In patients with cancer and acute venous thromboembolism, dalteparin was more effective than an oral anticoagulant in reducing the risk of recurrent thromboembolism without increasing the risk of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
1,424
15
63

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,305 publications
(1,556 citation statements)
references
References 22 publications
54
1,424
15
63
Order By: Relevance
“…Although robust randomized data in patients with malignancy and venous thromboembolism exist,34, 35 generalizability of these results to patients with AF has its limitations given different pathophysiological and risk profiles. The European Society of Cardiology recommends consideration of a DOAC as first‐line therapy in patients with AF for stroke prevention 13.…”
Section: Discussionmentioning
confidence: 99%
“…Although robust randomized data in patients with malignancy and venous thromboembolism exist,34, 35 generalizability of these results to patients with AF has its limitations given different pathophysiological and risk profiles. The European Society of Cardiology recommends consideration of a DOAC as first‐line therapy in patients with AF for stroke prevention 13.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increased risks of major bleeding during anticoagulation in fragile patients could be explained, at least in part, by these other drugs that might have potentiated the effect of the anticoagulant therapy. The similar risk for bleeding than for VTE recurrences in VTE patients weighing ≤50 kg has not been consistently reported 26, 27, 28. These findings suggest the potential benefit of tailored therapy for VTE according to clinical characteristics of the patients and warrant external validation.…”
Section: Discussionmentioning
confidence: 85%
“…In these studies, LMWH was compared to vitamin K antagonists (VKA) for the treatment of acute VTE in cancer patients. The pivotal CLOT study showed a significant reduction in VTE recurrence,4 while three other smaller studies showed no difference in efficacy or safety outcomes,30, 31, 32 and the most recent CATCH study33 showed a nonsignificant reduction in VTE recurrence, but a significantly decreased risk of clinically relevant non‐major bleeding (CRNMB) in the LMWH arm. We performed a meta‐analysis of the summary data from these studies using Review Manager (RevMan) [Computer program].…”
Section: Treatment Of Cancer‐associated Thrombosismentioning
confidence: 99%
“…Therefore, the optimal prevention and treatment of VTE are crucial components of patient care in this population. Low‐molecular‐weight heparin (LMWH), when compared with warfarin, has been shown to reduce the risk of recurrent VTE in patients with cancer‐associated thrombosis (CAT),4 and is therefore the standard treatment for acute CAT for the past 15 years. However, the high cost and significant lifestyle burden associated with LMWH have led many clinicians and investigators to wonder whether the direct oral anticoagulants (DOACs) might be a better choice for primary and/or secondary VTE prevention in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%